EFFECT OF HORMONAL CONTRACEPTIVES ON SERUM SEROTONIN IN FEMALES OF REPRODUCTIVE AGE GROUP - Faryal, Uzma; Rashid, Shazia; Hajra, Bibi; Hassan, Mukhtiar; Saqib, Javeria; Ali, Muhammad Afaq (Journal of Ayub Medical College Abbottabad, 2016)
Background: Many types of hormonal contraceptives are in use nowadays for example oral pills, emergency contraceptive pills, vaginal rings, implantable rods and injectable contraceptives (combined and progestogens only). The purpose of this study was to determine and compare serum serotonin levels in married fertile females of reproductive age group using hormonal contraceptives with non-contraceptive users. Methods: A total of 300 women were selected in the study. This cross sectional study included three groups; Group-1 (control), group-2 (combined oral contraceptive users) and group-3 (injectable contraceptive users). History and examination of subjects were recorded on pro forma. Levels of serum serotonin were measured using standard ELISA kits. Results were analysed by one way anova and a p-value 0.05% was taken as significant, using SPSS 16.0. Results: The mean age of the patients in group-1 was 30.4±6.1 years, group-2 was 28.9±4.9 and in group-3 was 2.5±6.8 years. For subjects in group-1, group-2 and group 3 the mean±SD concentration of serum serotonin was 160.68±53.27 ng/dl, 227.3±63.98 ng/dl and 118.19±31.32 ng/dl. A significant (p=0.00) difference was seen among three groups, i.e., group-1, group-2 and group-3. After applying Post HOC Tukey’s HSD, there was statistically no significant difference between group-1 and group-2 (p=0.956). Difference was seen between group-2 and group-3 (p=0.00), it was also significant between group-3 and group-1 (p=0.00). Conclusion: It was concluded that hormonal contraceptives affect the levels of serum serotonin. Background: Many types of hormonal contraceptives are in use nowadays for example oral pills, emergency contraceptive pills, vaginal rings, implantable rods and injectable contraceptives (combined and progestogens only). The purpose of this study was to determine and compare serum serotonin levels in married fertile females of reproductive age group using hormonal contraceptives with non-contraceptive users. Methods: A total of 300 women were selected in the study. This cross sectional study included three groups; Group-1 (control), group-2 (combined oral contraceptive users) and group-3 (injectable contraceptive users). History and examination of subjects were recorded on pro forma. Levels of serum serotonin were measured using standard ELISA kits. Results were analysed by one way anova and a p-value 0.05% was taken as significant, using SPSS 16.0. Results: The mean age of the patients in group-1 was 30.4±6.1 years, group-2 was 28.9±4.9 and in group-3 was 2.5±6.8 years. For subjects in group-1, group-2 and group 3 the mean±SD concentration of serum serotonin was 160.68±53.27 ng/dl, 227.3±63.98 ng/dl and 118.19±31.32 ng/dl. A significant (p=0.00) difference was seen among three groups, i.e., group-1, group-2 and group-3. After applying Post HOC Tukey’s HSD, there was statistically no significant difference between group-1 and group-2 (p=0.956). Difference was seen between group-2 and group-3 (p=0.00), it was also significant between group-3 and group-1 (p=0.00). Conclusion: It was concluded that hormonal contraceptives affect the levels of serum serotonin.